A Microcosm of American Exceptionalism: Eigth-Rocks in Ruby as Chosen People in Toni Morrison’s Paradise - Güngör, Pınar Süt (My University, 2023)
American exceptionalism, which has been supposed to have a divine historiography, accentuates and represents various aspects of Americanness that manifest destiny and strong challenges. Its sense of independence and moral superiority stems from the mythos that prioritizes its uniqueness and responsibility as part of its formation process. This ideology, in particular, suggests that the prior history of these people is pointed toward the “New World” in order to build and glamorize their distinctive future. This study offers an overview of the connection between the ideology of American exceptionalism and the 8-rock families, as chosen people, in Toni Morrison’s novel Paradise. Morrison, in Paradise, portrays a black immigration movement that demands a long-term imperial settlement modeled by white American society. Facing the failure of Reconstruction, her characters strive to maintain their freedom and independence through self-imposed, forceful segregation. The assumption that grounds the study, therefore, is that the 8-rock families, the founders of Ruby Town, pattern the ideological formation of American exceptionalism, despite their coal-black skin color and inferior status in cultural paradigms, by adopting a policy of racial segregation. The solidification, as in the American case, implies that self-proclaimed New Founders are responsible for building an independent and superior community that embraces the doctrines of disenfranchisement and racism in America. In addressing this reciprocity and its outcomes, Morrison has confirmed that just like good things, discrimination and ideas of superiority are learned, and Ruby residents have learned to use their skin color as a tool of domination.